Problem członkostwa Tureckiej Republiki Cypru Północnego w Unii Europejskiej - Kolarz, Stefania (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Despite the unresolved dispute over the proclamation of the Turkish Republic of Northern Cyprus, the Republic of Cyprus joined the European Community in 2004. TRNC was recognized only by Turkey which, unlike the EU, affirms that the north of the island, in the absence of effective control of the Republic of Cyprus, does not belong to the Union. What is the legal status of the TRNC in the Union and the impact of EU accession on resolving the dispute?
Keywords: de facto state; TRNC; Apostolides; Green Line Regulation